Essays on International Trade and Environment - Fu, Jintao (Université d'Ottawa | University of Ottawa, 2024)
This dissertation employ applied microeconomics techniques with a specific emphasis on international trade and environmental economics in China. In Chapter one, I investigates the impact of China environmental regulation since 2015 on middle-aged people’s health, using data from the China Family Pannel Studies (CFPS). My findings suggest a signifcantly positive impacts on health benefits. In Chapter two, I employs a Shift-Share instrument variable to investigate the long-term effect of China’s export expansions on human capital accumulation, highlighting the benefits of trade shocks and costs of trade-induced pollution shocks. In Chapter three, I study the causal relationship of international coal boom on human capital. My results show that the high school students in coal-abundant prefectures experience a significant reduction in university attainments and cognitive test scores and improvements in labor market outcomes.
Keywords: International Trade